IMPLIKASI HUKUM KEBIJAKAN LAND FREEZING DI IBU KOTA NUSANTARA TERHADAP PENYELESAIAN SENGKETA LAHAN TRANSMIGRASI SWAKARSA MANDIRI DAN PERUSAHAAN SAWIT - Uyun, Qurotul; Susmiyati, Haris Retno; Subroto, Aryo (Universitas Labuhanbatu, 2025)
The Independent Self-Supported Transmigration (TSM) program in Tengin Baru Village, Sepaku District, North Penajam Paser Regency is part of Indonesia's broader effort to promote equitable development and social welfare. However, its implementation has triggered land disputes between transmigrant communities and the palm oil company PT. Agro Indomas. The complexity of the conflict has increased due to the area's inclusion within the delineation of the Nusantara Capital City (IKN), which enforces a land freezing policy—restricting the transfer of land rights through various legal instruments. This study adopts a socio-legal research approach to evaluate the effectiveness of existing legal mechanisms in providing legal certainty for landowners and to identify the barriers faced by communities in asserting their land rights. The findings indicate that the land freezing policy is not supported by adequate dispute resolution instruments, resulting in prolonged legal uncertainty and weakening the position of transmigrant communities in claiming their land.Keywords: Disputes; IKN; Legal Certainty; Land Freezing; Swakarsa Mandiri Transmigration